A network analysis of global banking : 1978-2009 - Reyes, Javier; Minoiu, Camelia (Washington, D.C. : International Monetary Fund, 2011)
In this paper we explore the properties of the global banking network using cross-border bank lending data for 184 countries over 1978-2009. Specifically, we analyze financial interconnectedness using network metrics of centrality, connectivity, and clustering. We document a relatively unstable global banking network, with structural breaks in network indicators identifying several waves of capital flows. Interconnectedness rankings, especially for borrowers, are relatively volatile over the period. Connectivity tends to fall during and after systemic banking crises and sovereign debt crises. The 2008-09 global financial crisis stands out as an unusually large perturbation to the cross-border banking network.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet